2006
DOI: 10.1155/asp/2006/26503
|View full text |Cite
|
Sign up to set email alerts
|

Time Delay Estimation in Room Acoustic Environments: An Overview

Abstract: Time delay estimation has been a research topic of significant practical importance in many fields (radar, sonar, seismology, geophysics, ultrasonics, hands-free communications, etc.). It is a first stage that feeds into subsequent processing blocks for identifying, localizing, and tracking radiating sources. This area has made remarkable advances in the past few decades, and is continuing to progress, with an aim to create processors that are tolerant to both noise and reverberation. This paper presents a sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
220
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(220 citation statements)
references
References 66 publications
0
220
0
Order By: Relevance
“…Most of the conventional localization algorithms have been developed using a microphone array fixed at given positions [4,5,[8][9][10][11][12]15] and with constant directiondependent cues, on the assumption that a source position does not vary. The most commonly used time delay estimation (TDE) method is to use the generalized crosscorrelation (GCC) function, which is employed to estimate ICTD between the selected pair of microphones [16,17].…”
Section: Localization Cue: Ictd Trajectorymentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the conventional localization algorithms have been developed using a microphone array fixed at given positions [4,5,[8][9][10][11][12]15] and with constant directiondependent cues, on the assumption that a source position does not vary. The most commonly used time delay estimation (TDE) method is to use the generalized crosscorrelation (GCC) function, which is employed to estimate ICTD between the selected pair of microphones [16,17].…”
Section: Localization Cue: Ictd Trajectorymentioning
confidence: 99%
“…ICTD is defined as the time difference between the arrivals of a sound wave-front to the microphones; ICLD is defined as the difference between the sound pressure levels at the microphones; and ICSD means the difference between the spectral contents at the microphones. ICTD has been used as the most powerful localization cue [8][9][10] in almost all applications. Comparatively, ICLD and ICSD have not been used as frequently for practical applications, but are nevertheless employed in biomimetic research, including that of ear-based SSL systems [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It has attracted considerable research attention over the past few decades in different technologies including radar, sonar, seismology, geophysics, ultrasonics, communication and medical ultrasound imaging. Various techniques are reported in the literature (Knapp & Carter, 1976;Carter, 1979;1987;Boucher & Hassab, 1981;Chen et al, 2004) and a complete review can be found in (Chen et al, 2006). Chen et.al in their review consider critical techniques, limitations and recent advances that have significantly improved the performance of time-delay estimation in adverse environments.…”
Section: Time Delay and Distance Measurement Using Conventional Appromentioning
confidence: 99%
“…Moreover, the cross-correlation gives good performances when the signal-to-noise ratio (SNR) is high and the useful signal is slightly distorted. Thorough state-of-the-art reviews of cross-correlation-based TDOA estimators can be found in [8,9,10].…”
Section: Introductionmentioning
confidence: 99%